Additional figures in Ady Endre’s poem: A magyar Ugaron and in its English translations: The magyar fallow by Nyerges Anton and On the Hungarian fallow by Bernard Adams - KISS, TIMEA (Journal of Education Culture and Society, 2020)
My paper examines the figures of speech in English translations of Ady’s poem. The main organizers in Ady’s texts are repetition, parallelism, antithesis and other figures. The connection between these figures is an important component of his style. I examine whe-ther the translations are showing these figures, and if so, what their function is. The paper mostly concentrates on repetition in the translations. An analysis of one poem by Ady is presented through the translated texts.